2014
DOI: 10.1007/s00167-014-3168-1
|View full text |Cite
|
Sign up to set email alerts
|

Speed, not magnitude, of knee extensor torque production is associated with self-reported knee function early after anterior cruciate ligament reconstruction

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 48 publications
(61 reference statements)
3
54
0
Order By: Relevance
“…This decrease in isokinetic RTD supports previous theories of researchers 15,51 who suggested that a lower RTD may be determined by a lack of afferent feedback from the reconstructed ACL, ultimately inhibiting the recruitment of high-threshold motor units. A lower RTD may also indicate a longer period is needed for higher-threshold motor units to activate.…”
Section: Isokinetic Interlimb Asymmetriessupporting
confidence: 86%
See 3 more Smart Citations
“…This decrease in isokinetic RTD supports previous theories of researchers 15,51 who suggested that a lower RTD may be determined by a lack of afferent feedback from the reconstructed ACL, ultimately inhibiting the recruitment of high-threshold motor units. A lower RTD may also indicate a longer period is needed for higher-threshold motor units to activate.…”
Section: Isokinetic Interlimb Asymmetriessupporting
confidence: 86%
“…20,30 The TTP was calculated (TTP ¼ time of peak torque -time of onset of torque) for both isometric and isokinetic data. 15 A representation of how the isometric and isokinetic data were analyzed is shown in Figures 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 The ability to produce quick or explosive movements is often more important than muscle strength 19 in sporting activities, and speed rather than magnitude is associated with self-reported physical function in individuals with ACLR. 20 Therefore, the rate of torque development (RTD) is an important indicator of quadriceps function in individuals with ACLR 21 and is associated with greater ground reaction forces and loading rates during walking gait.…”
Section: à6mentioning
confidence: 99%